Gambaran Daya Terima terhadap Modifikasi Snack Puding Ubi Ungu Pisang Diabetes Melitus di Instalasi Gizi X: Overview of Acceptance of the Modified Purple Banana Pudding Snack Diabetes Mellitus in the Nutrition Installation of RS X - Mya Yemima Octaviani; Dhini Dhini; Munifa Munifa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Medical record data at RS X Central Kalimantan in 2022 found the number of DM cases in inpatient visits was 969 cases. Efforts to obtain healing from a disease, including type 2 DM with complications other than treatment, food is one of the supporting factors. snack DM RS X is a banana. Foods made from purple sweet potato flour can potentially be an alternative food for people with diabetes mellitus. Modification and standardization of the menu is changing the basic recipe into a new recipe to increase the nutritional value of a food and standardized it so that the quality and consistency are the same every time. The method in this research is qualitative with descriptive research type and cross sectional research design. The results of the research on the afternoon snack menu before modification were boiled banana kepok and after modification was banana purple sweet potato pudding. From the panelist's level of preference test for the aroma of banana purple sweet potato pudding very much like 14.29% and like 76.19%, for the purple banana sweet potato pudding color, really like 57.14% and like 38.10%, for the banana texture. Purple banana sweet potato liked 23.81% and liked 71.43%, as well as for the taste of banana purple sweet potato liked 9.52% and liked 76.19%.